Clinical and Biochemical Profile of Children with Chronic Kidney Disease in a Tertiary Care Hospital of Bangladesh (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Background: Chronic kidney disease (CKD) is an insidious and irreversible condition that eventually progresses to end stage renal failure and important cause of morbidity and mortality in children worldwide. However, the care of these patients represents a challenge for health care providers, which must pay attention not only to renal disease, but also to the various extra renal manifestations that affect growth and development. Evaluation of clinical and biochemical profile of children with chronic kidney disease can help to meet up this challenge.Methods:  This cross-sectional observational cohort study evaluated clinical, anthropometric and biochemical variables of children with chronic kidney disease aged 2 to 16 years in the department of Pediatric Nephrology, Dhaka Shishu (Children) Hospital, Bangladesh, during July’ 2018 to December’ 2018. A total of thirty-six children with chronic kidney disease with creatinine clearance